2010
DOI: 10.1002/dvdy.22443
|View full text |Cite
|
Sign up to set email alerts
|

White adipose tissue development in zebrafish is regulated by both developmental time and fish size

Abstract: Adipocytes are heterogeneous. Whether their differences are attributed to anatomical location or to different developmental origins is unknown. We investigated whether development of different white adipose tissue (WAT) depots in zebrafish occurs simultaneously or whether adipogenesis is influenced by the metabolic demands of growing fish. Like mammals, zebrafish adipocyte morphology is distinctive and adipocytes express cell-specific markers. All adults contain WAT in pancreatic, subcutaneous, visceral, esoph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
128
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 115 publications
(132 citation statements)
references
References 35 publications
3
128
1
Order By: Relevance
“…Previous studies have shown that zebrafish adipocytes and AT are morphologically, molecularly, and functionally homologous to mammalian white AT (21-26), and like mammals, zebrafish adipocytes accumulate a large cytoplasmic lipid droplet (LD) that facilitates the in vivo identification of adipocytes by fluorescent lipophilic dyes (21,22,(24)(25)(26). Here we determine in zebrafish that Plxnd1 functions through Col5a1 to exert a VAT-specific effect on adipose growth and morphology, resulting in altered body fat distribution and improved insulin sensitivity.…”
mentioning
confidence: 99%
“…Previous studies have shown that zebrafish adipocytes and AT are morphologically, molecularly, and functionally homologous to mammalian white AT (21-26), and like mammals, zebrafish adipocytes accumulate a large cytoplasmic lipid droplet (LD) that facilitates the in vivo identification of adipocytes by fluorescent lipophilic dyes (21,22,(24)(25)(26). Here we determine in zebrafish that Plxnd1 functions through Col5a1 to exert a VAT-specific effect on adipose growth and morphology, resulting in altered body fat distribution and improved insulin sensitivity.…”
mentioning
confidence: 99%
“…At 15 dpf, expression of the gene for PPARy was detected in terminally differentiated adipocytes located in the pancreas (which shows that it can be used as a marker for these cells), and in cells of the intestinal epithelium (Flynn et al 2009). In adult fish, expression of this gene was observed in liver, pancreas and visceral adipose tissue (Imrie & Sadler 2010). Immunohistochemistry revealed that PPARα, PPARÎČ and PPARÎł are all widely expressed after 7 dpf, and that for all isoforms, the expression level in liver is higher in early developmental stages than in adults (Ibabe et al 2005).…”
Section: The Zebrafish Peroxisome Proliferatoractivated Receptors (Ppmentioning
confidence: 98%
“…However the postembryonic development of adipose tissue is influenced by environmental and metabolic factors (Imrie & Sadler, 2010). Nevertheless, fish stock lipid in adipose tissue located around the digestive tract, under the skin, the meat between the myomeres and in the myomeres (Fauconneau, Corraze, Lebail, & Vernier, 1991).…”
Section: Introductionmentioning
confidence: 99%